Empowerment for Patients with Depressive Disorders: Role of Psychiatric Nurses - Wongjumpa, Suparada; thamduangsri, pattarin (Princess of Naradhiwas University Journal, 2025)
The purpose of this scholarly article was to provide information regarding empowerment for patients with depressive disorder. The researcher used the empowerment process to modify nursing care activities for patients with depressive disorder. The activity was created by focusing on problem-solving to address the current issue and improve the patients’ sense of self-worth and develop appropriate behavior in order to improve the self-empowerment of patients with depressive disorder and enable them to live happily in society